Understanding acute burn injury as a chronic disease. Issue 1 (16th September 2019) - Barrett, Lucy W.; Fear, Vanessa S.; Waithman, Jason C.; Wood, Fiona M.; Fear, Mark W.
Abstract: While treatment for burn injury has improved significantly over the past few decades, reducing mortality and improving patient outcomes, recent evidence has revealed that burn injury is associated with a number of secondary pathologies, many of which arise long after the initial injury has healed. Population studies have linked burn injury with increased risk of cancer, cardiovascular disease, nervous system disorders, diabetes, musculoskeletal disorders, gastrointestinal disease, infections, anxiety and depression. The wide range of secondary pathologies indicates that burn can cause sustained disruption of homeostasis, presenting new challenges for post-burn care. Understanding burn injury as a chronic disease will improve patient care, providing evidence for better long-term support and monitoring of patients. Through focused research into the mechanisms underpinning long-term dysfunction, a better understanding of burn injury pathology may help with the development of preventative treatments to improve long-term health outcomes. The review will outline evidence of long-term health effects, possible mechanisms linking burn injury to long-term health and current research into burns as a chronic disease.